Mineral medicines of the East: an analysis of records in historical Chinese and Japanese medical texts - Dai, Min; Wang, Ding (Frontiers in Pharmacology, 2025)
BackgroundTraditional Chinese medicine (TCM) in China and Kampo medicine in Japan are representative forms of traditional medicine in East Asia, in which mineral medicines constitute an indispensable source of therapeutic agents. Due to concerns about toxicity and safety, the frequency of mineral medicine use in modern times has declined compared with historical practice. Existing research on mineral medicines in traditional medicine has predominantly focused on toxicity and safety issues in an international context, overviews of historical mineral medicines in Japan, or records of specific mineral medicines in single ancient medical texts in China. However, there is a lack of comparative studies spanning multiple countries, historical periods, and a wide range of historical medical literature.MethodsThis study utilized modern computational techniques and a self-constructed database, the Chinese–Japanese Traditional Medical Literature Corpus. Based on the medical history of China and Japan, 56 representative historical medical texts from the period 219–1863 were selected, from which data on mineral medicines were extracted. The methods of prescription metrology and data mining were applied to analyze the co-occurring medicines in prescriptions containing mineral medicines, while word frequency statistics were used to examine the conditions treated by these medicines. Data cleaning, statistical analysis, and visualization were performed using Microsoft Excel and Python scripts.ResultsThe “Prescription” category of historical medical texts is the primary source of mineral medicine data for both countries. A total of 106 mineral medicines were recorded in Chinese historical texts, compared with 100 in Japanese historical texts, with 97 mineral medicines shared between the two. Based on a cation-based classification system, the mineral medicines documented in the historical texts of China and Japan were divided into 16 categories; all 16 were found in Chinese texts, while Japanese texts contained 14 categories. The top three categories of mineral medicines by number of occurrences were the same in both countries, though their ranking order differed slightly. For pharmacological analysis, mercury- and mercury-compound-based mineral medicines (hereafter referred to as mercury-based mineral medicines) were selected due to their high toxicity and high number of occurrences. Historical Chinese texts recorded 189 medical conditions treated with mercury-based mineral medicines or compound prescriptions containing them, while Japanese texts recorded 98 such conditions, with two conditions unique to Japan. Six conditions were identified as core conditions strongly associated with mercury-based mineral medicines in both countries. Historical Chinese texts documented 257 co-occurring medicines with mercury-based mineral medicines, while Japanese texts recorded 240, with 17 species unique to Japan. Twelve co-occurring medicines were identified as core drugs strongly paired with mercury-based mineral medicines in both countries. Gypsum was selected for further pharmacological analysis, as it is included in both modern authoritative pharmacopoeias and ranks just below salt in number of occurrences in historical texts of both countries. Historical Chinese texts documented 429 co-occurring medicines with gypsum, while Japanese texts recorded 168. The core medicines strongly paired with gypsum showed minimal differences between the two countries. The top five conditions most strongly associated with gypsum, in terms of number of occurrences, were the same in both Chinese and Japanese historical texts, although their ranking varied slightly. Compared with the indications recorded in modern pharmacopoeias and medical literature of both countries, the descriptions of gypsum-related core conditions in historical texts were more diverse and detailed.ConclusionThe classification of historical medical texts in this study is based on the characteristics of their content. The types of historical texts serving as data sources for mineral medicines are similar in China and Japan, and the recorded mineral medicine species, compound types, and frequently recorded varieties also show a high degree of similarity, indicating that Kampo medicine in Japan extensively absorbed the theoretical foundations of mineral medicines from TCM. However, the higher number of occurrences of sodium compound–based mineral medicines in Japan, as well as the differences in the occurrence probabilities of commonly recorded mineral medicines between the two countries, to some extent reflect the localization tendencies of mineral medicine use in Kampo medicine. Mercury-based mineral medicines and gypsum documented in historical Chinese and Japanese medical texts showed minimal differences in associated conditions and co-occurring medicines. Many mercury-based mineral medicines shared generalizable features, highlighting the research significance and value of distinguishing mineral medicines by compound type to reveal overarching pharmacological trends. The comparison of gypsum’s principal therapeutic indications between historical and modern records revealed a clear trend toward a narrower application scope for mineral medicines in the modern era. From the perspective of preserving and inheriting traditional mineral medicine knowledge, a large amount of mineral medicine knowledge in historical Chinese and Japanese medical texts remains to be explored. Furthermore, research supported by objective data—such as analyses of the pharmacological effects of co-occurring medicines related to mineral medicines and studies on the associations between these co-occurring medicines and their related conditions—remains urgently needed.